High Availability and Disaster Recovery in SQL Server: Implementing Always On Solutions for Enterprise Resilience - Siva Kumar Raju Bhupathiraju (International Journal of Scientific Research in Computer Science, Engineering and Information Technology, 2025)
This comprehensive technical article explores SQL Server’s high availability and disaster recovery solutions, focusing on Always On Availability Groups and Failover Clustering. It presents the architectural foundations, implementation methodologies, and strategic considerations for establishing resilient database environments. The article progresses through detailed discussions of replication models, multi-subnet configurations, and failover strategies while examining the critical role of Windows Server Failover Clustering. Advanced topics include geo-replication approaches, hybrid cloud implementations, and performance optimization techniques for minimizing latency in distributed environments. Through architectural guidance, implementation best practices, and real-world case studies, this resource equips database administrators and IT architects with the knowledge to design and maintain fault-tolerant SQL Server infrastructures that ensure business continuity, operational resilience, and data integrity for mission-critical applications.